PENERAPAN MANAJEMEN KELAS UNTUK MENINGKATKAN MINAT BELAJAR SISWA KELAS V SD NEGERI 2 BONE-BONE - Yurfiah Yurfiah; Kosilah Kosilah; Wa Ode Nurul Haryati (Jurnal Inovasi Penelitian, 2023)
The purpose of this research is to determine the implementation of classroom management to enhance the students' interest in learning in Grade V of State Elementary School 2 Bone-Bone. This study is a field research using a qualitative descriptive method. Qualitative descriptive method involves describing data using words that correspond to the obtained data. The data collection techniques used in this research include observation, interviews, and documentation study. These three techniques are utilized to obtain the expected data. The research findings conclude that prior to teaching, teachers should create a classroom management plan and implement it through the application of classroom management principles and approaches, while consistently monitoring classroom management by considering factors and obstacles. Specifically, the research findings can be described as follows: 1) Classroom management planning should be carried out by creating a plan before entering the classroom; 2) Classroom management implementation aims to establish a good relationship with the school community by applying the principles of warmth and enthusiasm, challenge, variety, appreciation, emphasizing positive aspects, and discipline; 3) Ongoing supervision is conducted by the school principal over the teaching process; 4) Supportive and inhibiting factors significantly influence classroom management by teachers